Clinical and Radiological Outcomes of Corrective Surgery on Adult Spinal Deformity Patients: Comparison of Short and Long Fusion - Koichiro Ono; Kazuo Ohmori; Takeshi Hori (Advances in Orthopedics)
Despite the accumulated knowledge of spinal alignment and clinical outcomes the full corrective surgery cannot be applied to all the deformity patients as it requires considerable surgical burden to the patients. The aim of this study was to investigate the clinical and radiological outcomes of the patients who have received short and long fusion for ASD. A total of 21 patients who received surgical reconstructive spinal fusion procedures and were followed up for at least one year were retrospectively reviewed. Sixteen cases have received spinal corrective surgery that upper instrumented vertebrate (UIV) was thoracic level (group T), or 5 cases were with UIV in lumbar level (group L). Group L had shorter operation time, smaller intraoperative estimated blood loss, and shorter postoperative hospitalization days. Group T tends to improve more in the magnitude of VAS of lumbar pain compared to group L. Improvement of spinal alignment revealed the advantage of long fusion compared to short fusion, in Cobb angle, sagittal vertical axis (SVA), lumbar lordosis (LL), PI-LL C7 plum line (C7PL), and center sacral vertebral line (CSVL). Pelvic tilt (PT) did not differ between the groups. Disc lordosis was the most acquired in XLIF compared to TLIF and PLF and maintained one year. There were 9 adverse events, 3 cases of pulmonary embolism (PE), one case of delirium, and 6 cases of proximal junctional kyphosis. Current study elucidated that long fusion, UIV, is thoracic and can achieve better spinal alignment compared to short fusion, UIV, in lumbar. XLIF demonstrated strong ability to reconstruct the deformity on intervertebral space that is better to apply as much intervertebral space as possible. For the ASD patients with complications, short fusion can be one of the options.